Pengaruh Komunikasi Internal, Kepemimpinan Transformasional, Kerja Sama Tim, dan Disiplin Kerja Terhadap Kinerja Generasi Z Pada PT Drg Rama Boga - Gusti Ayu Puji Susanti; I Wayan Ardhi Wirawan; Ni Luh Sinar ayu Ratna Dewi (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relations, 2026)
This study aims to analyze the influence of internal communication, transformational leadership , teamwork, and work discipline on the performance of generation Z at PT Drg Rama Boga. This study uses an associative quantitative approach. The study population was 59 people with a sample of 50 people determined using a purposive sampling technique. The data collection technique was carried out by distributing research questionnaires with data analysis techniques using multiple linear regression analysis with the help of the IBM SPSS version 27 program. The results of the study showed that from the results of the t-test, internal communication and teamwork had a positive and insignificant effect, transformational leadership had no significant effect, while work discipline had a positive and significant effect. Based on F test results, in general together internal communication, leadership transformational, work The same team and discipline Work influential to performance generation Z. Adjusted R Square Value of 0.756 or 75.6%. This result show that internal communication, leadership transformational, work the same team and discipline work capable influence performance generation Z at PT Drg Rama Boga is 75.6% while the rest 24.4 % is explained by other variables outside variables study This.